M subdwarf research: III. spectroscopic diagnostics for breaking parameter degeneracy - Zhang, Shuo; Zhang, Hua-Wei; Comte, Georges; Homeier, Derek; Wang, Rui; Hejazi, Neda; Li, Yin-Bi; Luo, A-Li (The astrophysical journal, 2023)
To understand the parameter degeneracy of M subdwarf spectra at low resolution, we assemble a large number of spectral features in the wavelength range 0.6-2.5 μm with band strength quantiﬁed by narrowband indices. Based on the index trends of BT-Settl model sequences, we illustrate how the main atmospheric parameters (Teff, log g, [M/H], and [α/Fe]) affect each spectral feature differently. Furthermore, we propose a four-step process to determine the four parameters sequentially, which extends the basic idea proposed by Jao et al. Each step contains several spectral features that break the degeneracy effect when determining a speciﬁc stellar parameter. Finally, the feasibility of each spectroscopic diagnostic with different spectral quality is investigated. The result is resolutionindependent down to R ∼ 200.
Gesehen am 13.03.2023